The bounds of reason : game theory and the unification of the behavioral sciences - Gintis, Herbert (Princeton University Press, 2009)
Game theory is central to understanding human behavior and relevant to all of the behavioral sciences--from biology and economics, to anthropology and political science. However, as The Bounds of Reason demonstrates, game theory alone cannot fully explain human behavior and should instead complement other key concepts championed by the behavioral disciplines. Herbert Gintis shows that just as game theory without broader social theory is merely technical bravado, so social theory without game theory is a handicapped enterprise.